A comment on Xu (2022). Reshaping Global Trade: The Immediate and Long-Term Effects of Bank Failures - Guillaume Bérard; Dimitria Freitas; Priyam Verma (Institute for Replication (I4R), 2023)
Xu (2022) estimates the causal impact of bank failures on the level of trades with a staggered difference-in-differences design and an IV strategy with Bartik instrument, using the 1866 banking crisis as a quasi-natural experiment. Findings, based on historical data on the trades and loans between London banks and banks around the world, show that countries exposed to bank failures in London immediately exported significantly less and did not recover their lost growth relative to unexposed places. Moreover, the effect lasted for decades. First, we reproduce the paper's main findings by running the original code and uncover three issues, one of which that slightly affects the main estimates reported in the study. Second, we test the robustness of the results to (1) removing weights from the regressions, (2) using a spatial HAC correction for the standard errors, and (3) implementing a method for possibly heterogeneous treatment effects with a staggered difference-indifferences design. Overall, we conclude that the main findings are valid and robust.
Keywords: F14; G01; G21; N20; 330; Replication; Robustness; Trade; Bank failures; Historical data; Difference-in-differences